Rancang Bangun Aplikasi Pengarsipan Surat Masuk dan Surat Keluar Menggunakan Metode Waterfall: Studi Kasus pada Kantor Camat Ciputat Timur - Trisnayanti; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This study aims to overcome problems in filing letters at the East Ciputat District Office. The filing process that is done manually causes misplacement and search of letters, disrupts employee productivity, and requires a lot of time and effort. The waterfall method will be used in developing web-based mail archiving applications. The purpose of this research is to increase the effectiveness and efficiency of filing letters by reducing errors and speeding up letter search. In addition, the goal is to prevent loss or damage to mail data, improve employee performance, and create a transparent mail filing system with minimal data processing errors. This research will use data collection methods through observation, interviews, and literature study. The system development method used is the waterfall method, which includes requirements analysis, system design, implementation, unit testing, and overall system testing. It is hoped that the results of this study can make a significant contribution in increasing the effectiveness and efficiency of letter filing, improving employee performance, and reducing data processing errors at the East Ciputat Sub-District Office. The use of a web-based mail filing application is also expected to speed up access and search for mail, thereby increasing work efficiency in the office. In addition to direct benefits for offices and employees, this research also provides benefits for writers in increasing knowledge and graduation, as well as benefits for agencies and universities in increasing the effectiveness of letter filing and the quality of writing.